2002
DOI: 10.1111/1467-839x.00092
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and social effects in allocation behavior: A new view on loci of developmental differences

Abstract: Allocations become more equitable with age in America but not in Asia. The authors hypothesized that age affects perception of inputs but a combination of perceived inputs and social value determines allocation behavior. The subtractive model guided data gathering from Chinese in Singapore. Experiment 1 confirmed the Asian age-trend, and demonstrated age differences in perceived inputs. Rated importance of perceived inputs decreased but that of group harmony increased from 5 to 17 years. In Experiment 2, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…In a series of studies, Singh and colleagues [Sin & Singh, 2005;Singh & Huang, 1995;Singh, Chong, Leow, & Tan, 2002] demonstrated that Chinese children and adolescents adjust their outcome allocations in concord with the Asian social value of maintaining group harmony, with younger children making more equitable and adolescents more equal allocations. In contrast, in Western cultures, cognitive developmental factors, such as the ability to calculate proportions, go hand in hand with the understanding of the social value of 'each according to his merit,' which consequently leads to an increase in equity judgments over the course of development.…”
Section: Economic Game Theory and The Development Of Distributive Jusmentioning
confidence: 99%
“…In a series of studies, Singh and colleagues [Sin & Singh, 2005;Singh & Huang, 1995;Singh, Chong, Leow, & Tan, 2002] demonstrated that Chinese children and adolescents adjust their outcome allocations in concord with the Asian social value of maintaining group harmony, with younger children making more equitable and adolescents more equal allocations. In contrast, in Western cultures, cognitive developmental factors, such as the ability to calculate proportions, go hand in hand with the understanding of the social value of 'each according to his merit,' which consequently leads to an increase in equity judgments over the course of development.…”
Section: Economic Game Theory and The Development Of Distributive Jusmentioning
confidence: 99%
“…Studies comparing Asian and Western resource distribution principles often find that equality is preferred over merit-based sharing in Asian and collectivist cultures (Bond, Leung & Wan, 1982;Rochat et al 2009;Thomson, 2007). This increases with age, with Singaporean children from five to 17 years moving from equity to equality based distribution (Singh, Chong, Leow & Tan, 2002). Future studies may also consider whether the integration of individual and group outcome differs in cultures where group harmony has higher social value.…”
Section: Group Structurementioning
confidence: 99%